The Relationship between Teachers' Perceptions of Compliance with the Psychological Contract and School Administrators' Empowering Leadership Behaviors - Gökyer, Necmi; Okay, İlkay; Okay, Berkay; Gökyer, Umran (Asya Publishing and Consultancy, 2023)
The aim of this study is to determine the relationship between school administrators' empowering leadership behaviors and secondary education (high school) teachers' perceptions of compliance with the psychological contract. The population of the study consists of 2,878 teachers who were working at 47 high schools located in central Elazığ during the 2019–2020 school year. The sample for the study consisted of 470 teachers selected from 12 schools using the stratified sampling method. Data were collected using the "Scale for School Administrator Compliance with Psychological Contract" developed by Koçak (2016) and the "Scale for Teacher Compliance with Psychological Contract". Teacher perceptions of the level to which school administrators displayed empowering leadership behaviors were measured using the Empowering Leadership Behaviors Scale developed by Konczak, Stelly, and Trusty (2000) and adapted to Turkish by Aras (2013). It was found that teachers had high perceptions of school administrator compliance with the psychological contract (SACPC) and that they also had a high level of compliance with the psychological contract (STCPC). Additionally, it was found that teacher perceptions of school administrators displaying empowering leadership behaviors (OYGLD) were also high. Perceptions of teachers who had been working for 7–11 years in the same school regarding school administrator compliance with the psychological contract were higher than those of teachers who had been working in the same institution for 2–6 years. A moderately positive and significant relationship was found between school administrators' and teachers' compliance with the psychological contract and administrators' empowering leadership behaviors. Reinforcing the leadership behaviors of school administrators; does not have a significant effect on coaching sub-dimensions for decision-making, knowledge sharing, and innovative performance on its own. © 2023, Asya Publishing and Consultancy. All rights reserved.
Keywords: Compliance with psychological contract; Employee empowerment; Empowering leadership behaviors; Psychological contract